2003
DOI: 10.1046/j.1365-2486.2003.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of carbon and nitrogen by old arable land reverting to woodland

Abstract: The accumulation of carbon (C) and nitrogen (N) was measured on two sites on Rothamsted Farm that had been fenced off some 120 years ago and allowed to revert naturally to woodland. The sites had previously been arable for centuries. One had been chalked and was still calcareous; the other had never been chalked and the pH fell from 7.1 in 1883 to 4.4 in 1999. The acidic site (Geescroft wilderness) is now a deciduous wood, dominated by oak (Quercus robor); the calcareous site (Broadbalk wilderness) is now domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 40 publications
(58 reference statements)
8
97
1
9
Order By: Relevance
“…1) with the same units (replacing 'root' with 'SOC' or 'TN'). Following others [18,31], we used an 'equivalent soil mass' approach to adjust the measured SOC and TN density of the initial baseline data to that based on the bulk density measured after 4 and 6 years, which did not differ significantly. For only the soils collected from Miscanthus plots, the 13 C/ 12 C stable isotope ratios were quantified on prepared carbonate-free soil [23] with an IsoPrime 100 Stable Isotope Ratio Mass Spectrometer (Isoprime Ltd., Cheadle Hulme, UK) coupled with a Vario MICRO Cube Elemental Analyser (Elementar Analysensysteme GmbH, Langenselbold, Germany).…”
Section: Soil Analysismentioning
confidence: 99%
“…1) with the same units (replacing 'root' with 'SOC' or 'TN'). Following others [18,31], we used an 'equivalent soil mass' approach to adjust the measured SOC and TN density of the initial baseline data to that based on the bulk density measured after 4 and 6 years, which did not differ significantly. For only the soils collected from Miscanthus plots, the 13 C/ 12 C stable isotope ratios were quantified on prepared carbonate-free soil [23] with an IsoPrime 100 Stable Isotope Ratio Mass Spectrometer (Isoprime Ltd., Cheadle Hulme, UK) coupled with a Vario MICRO Cube Elemental Analyser (Elementar Analysensysteme GmbH, Langenselbold, Germany).…”
Section: Soil Analysismentioning
confidence: 99%
“…Additionally, most of the available studies were conducted in Amazonia or North America and there is large variability in physical and biotic characteristics as well as in land management (Kauffman et al, 2009). Many studies focus on the recovery of biodiversity or species richness (Cramer et al, 2008;Queiroz et al, 2014), but these variables cannot be adequately captured by our large-scale PFT approach. It is often assumed that the ecosystem will gradually return to its previous state and that intensive LU delays recovery but the timescales are widely unknown and differ across variables and regions, e.g., tropical species composition recovers much slower than forest structure and soil nutrients (Chazdon, 2003).…”
Section: Comparison To Observations and Previous Studiesmentioning
confidence: 99%
“…Analyses of the long-term effects of historical LU are often limited by the availability of adequate LU information and the absence of undisturbed ecosystems, and usually rely on chronosequences (Chazdon, 2003;Knops and Tilman, 2000). Only a few long-term observational study plots like the one maintained at the Rothamsted Experimental Station (e.g., Poulton et al, 2003) exist. Differences between (near) pristine and post-agricultural forests or grasslands have been reported to persist for decades or centuries after agricultural abandonment for various variables, including soil pH (Falkengren-Grerup et al, 2006); microbial communities (Fichtner et al, 2014); soil C, N and phosphorus (Compton and Boone, 2000); and other nutrients (Wall and Hytonen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…3). The greater accumulation of plant debris by the revegetation and the slower rate of organic matter decomposition by the lack of cultivation might have contributed to the build up of soil organic carbon (SOC) in the buffer soils (Reddy et al, 2008). There was a significant relationship between SOC and N at the research area (r = 0.944, P < 0.01).…”
Section: Land-use Effects On Soil Physicochemical Propertiesmentioning
confidence: 97%
“…There was a significant relationship between SOC and N at the research area (r = 0.944, P < 0.01). Several studies have indicated that the rate of SOC accumulation is controlled by the rate of N accumulation in the early stages of vegetation regeneration of abandoned agricultural soils (Knops et al, 2000;Poulton et al, 2003). Differences of SOC and N between the crop and the buffer soils were less significant as depth increased at the HG and XL sites but increased at the NL sites.…”
Section: Land-use Effects On Soil Physicochemical Propertiesmentioning
confidence: 99%